Impact of tapering targeted therapies (bDMARDs or JAKis) on the risk of serious infections and adverse events of special interest in patients with rheumatoid arthritis or spondyloarthritis: a systematic analysis of the literature and meta-analysis - Vinson, D; Molet-Benhamou, L; Degboé, Y; den Broeder, A; Ibrahim, F; Pontes, C; Westhovens, R; Závada, J; Pham, T; Barnetche, T; Constantin, A; Ruyssen-Witrand, A (Arthritis research & therapy, 2020)
OBJECTIVES: To systematically review the impact of tapering targeted therapies (bDMARDs or JAKis) on the risk of serious infections and severe adverse events (SAEs) in patients with rheumatoid arthritis (RA) or axial spondyloarthritis (axSpA) in remission or low disease activity (LDA) state. MATERIALS AND METHODS: A meta-analysis based on a systematic review of PubMed, Embase, Cochrane, until August 2019, as well as relevant databases of international conferences, was used to evaluate the risk difference (RD) at 95% confidence interval (95% CI) of incidence density of serious infections, SAEs, malignancies, cardiovascular adverse events (CV AEs), or deaths after tapering (dose reduction or spacing) compared to continuation of targeted therapies. RESULTS: Of the 1957 studies initially identified, 13 controlled trials (9 RA and 4 SpA trials) were included in the meta-analysis. 1174 patient-years were studied in the tapering group (TG) versus 1086 in the usual care group (UC). There were 1.7/100 patient-year (p-y) serious infections in TG versus 2.6/100 p-y in UC (RD (95% CI) 0.01 (0.00 to 0.02), p = 0.13) and 7.4/100 p-y SAEs in TG versus 6.7/100 p-y in UC (RD 0.00 (- 0.02 to 0.02), p = 0.82). The risk of malignancies, CV AEs, or deaths did not differ between the tapering and the usual care groups. Subgroup analysis (RA and SpA) detected no significant differences between the two groups. CONCLUSION: We could not show significant impact of tapering bDMARD or JAKi over continuation concerning the risk of serious infections, SAEs, malignancies, CV AEs, or deaths in RA and SpA patients in remission or LDA state.
Keywords: Janus Kinases; Spondyloarthritis; lidé; Infection bacteria; spondylartritida; Rheumatoid arthritis; Viruses infection; Arthritis, Rheumatoid; Humans; Janus kinasy; DMARDs; klinické zkoušky kontrolované jako téma; antirevmatika; Biological therapies; Systematic review; revmatoidní artritida; Biological Products; inhibitory TNF; Antirheumatic Agents; Controlled Clinical Trials as Topic; Spondylarthritis; Tumor Necrosis Factor Inhibitors; biologické přípravky